Least square-based vehicle position estimation algorithm - PENG Xin; LI Ren-fa; YANG Liu; LIU Liang-jiao (Tongxin xuebao)
A vehicle position estimation algorithm base on least square optimization was prposed.Firstly,the algorithm deduced the convex constraint condition which the distance matrix had to conform within a short time interval.Then,the least square method was employed to estimate the vehicles’ relative position.Finally,the local maps were merged into the global map.Simulation results demonstrate that the algorithm can achieve preferable estimation accuracy,and meet the real time constraint in vehicular networks.